Anti-inflammatory and Pro-apoptotic Effects of 18beta-Glycyrrhetinic Acid In Vitro and In Vivo Models of Rheumatoid Arthritis - Feng, Yunhui; Mei, Liyan; Wang, Maojie; Huang, Qingchun; Huang, Runyue (Frontiers in Pharmacology, 2021)
18β-Glycyrrhetinic acid (18β-GA), an active component from Glycyrrhiza glabra L. root (licorice), has been demonstrated to be able to protect against inflammatory response and reduce methotrexate (MTX)-derived toxicity. This study was therefore designed to test the therapeutic possibility of 18β-GA on rheumatoid arthritis (RA) and to explore the underlying mechanism. LPS or TNF-α-induced inflammatory cell models and collagen-induced arthritis (CIA) animal models were applied in this study. Real-time quantitative PCR (RT-qPCR) was used to measure the mRNA levels of various cytokines and FOXO family members. The protein levels of molecules in the MAPK/NF-κB signaling pathway were analyzed using western blot. The cell proliferation assay and colony-forming assay were used to test the influence of 18β-GA on cell viability. The cell apoptosis assay and cell cycle assay were performed to detect the effect of 18β-GA on cell proliferative capacity by using flow cytometry. Hematoxylin and eosin (H&E) staining was performed to evaluate pathological changes after drug administration. The enzyme-linked immunosorbent assay (ELISA) was carried out for the detection of cytokines in serum. In vitro, we found that 18β-GA decreased the mRNA levels of IL-1β, IL-6, and COX-2 by inhibiting the MAPK/NF-κB signaling pathway in MH7A and RAW264.7 cell lines. Moreover, 18β-GA was able to suppress cell viability, trigger cell apoptosis, and G1 phase cell cycle arrest in our in vitro studies. 18β-GA dramatically enhanced the mRNA level of FOXO3 in both TNF-α- and LPS-induced inflammation models in vitro. Interestingly, after analyzing GEO datasets, we found that the FOXO3 gene was significantly decreased in the RA synovial tissue as compared to healthy donors in multiple microarray studies. In vivo, 18β-GA exhibited a promising therapeutic effect in a collagen-induced arthritis mouse model by alleviating joint pathological changes and declining serum levels of TNF-α, IL-1β, and IL-6. Finally, we observed that 18β-GA administration could mitigate liver damage caused by collagen or MTX. Collectively, the current study demonstrates for the first time that 18β-GA can inhibit inflammation and proliferation of synovial cells, and the underlying mechanism may be associated with its inhibition of MAPK/NF-κB signaling and promotion of FOXO3 signaling. Therefore, 18β-GA is expected to be a new drug candidate for RA therapy.